Financial Performance of Banking Companies on IDX Before as Well as During the Covid-19 Pandemic - Martinus Budiantara; Ratri Paramitalaksmi; Fiki Rihadani (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to determine the financial performance on 44 bank company listed by IDX (Indonesian Stock Exchange) before as well as after the Covid-19 pandemic’s period using Operating Expenses and Operating Income (BOPO), Return On Asset (ROA), Non Performing Loan (NPL), also Capital Adequacy Ratio (CAR) variables and comparative quantitative methods, with difference test analysis tools Paired Simple T-Test and Sign-Wixolcon. The ratio of CAR and NPL was categorized as safe before as well as after the Covid-19 pandemic’s period, and its contrast to the ratio of ROA and BOPO. On the other hand, during the period of Covid-19 pandemic, ROA, CAR and NPL experienced an increase in performance while BOPO experienced a decrease in performance. The results are the ratio of CAR, ROA and NPL showed a sig difference, while the BOPO ratio did not show any sig differences in 44 banking company that listed on the IDX before as well as during the Covid-19 pandemic’s period. According to this, it is recommended that bank management in Indonesia can better control the company's operations more efficiently in future and subsequent research adds a wider sample and increases the duration of the study.